2009
DOI: 10.1002/ca.20747
|View full text |Cite
|
Sign up to set email alerts
|

The palmaris longus muscle and its relations with the antebrachial fascia and the palmar aponeurosis

Abstract: The palmaris longus (PL) is a muscle of the forearm with a long distal tendon that is continuous with the palmar aponeurosis (PA). It is generally assumed that the muscle lies deep to the antebrachial fascia from origin to termination, but a detailed description is lacking. The relationship of the PL tendon with the antebrachial fascia was studied in 30 dissections. The PL was completely absent in six specimens (20%), whereas the PA was identified in all. Average length of the forearm was 25.5 cm (SD: 2.1 cm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…It is located in the most superficial layer of the anterior compartment of the forearm, between the radial and the ulnar flexors of the wrist [4]. In most cases, the distal tendon of the PLM shows a lateral slip that attaches to the superficial surface of the abductor pollicis brevis muscle that may contribute to thumb abduction [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is located in the most superficial layer of the anterior compartment of the forearm, between the radial and the ulnar flexors of the wrist [4]. In most cases, the distal tendon of the PLM shows a lateral slip that attaches to the superficial surface of the abductor pollicis brevis muscle that may contribute to thumb abduction [5].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the distal tendon of the PLM shows a lateral slip that attaches to the superficial surface of the abductor pollicis brevis muscle that may contribute to thumb abduction [5]. In the proximal part of the forearm, the PLM is situated deep to the antebrachial fascia, while in the lower third of the forearm its tendon perforated the antebrachial fascia [4]. The origin of the PLM is at the epicondylus medialis of the humerus and the insertion is on the aponeurosis Palmaris [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Ito et al reported palmaris longus length 124.6±17 mm and width 4.5±0.7 in male, and 108.3±16.4 mm and width 4±0.7 in female. [25] Kopuz reported bilateral absence in 40.4% and unilateral absence in 8.5% and palmaris longus length 41.1 mm and width 1.7 mm in fetuses.…”
Section: Discussionmentioning
confidence: 96%
“…It continues with its tendon, which is long and flat, at the middle third level of the forearm. At this level, the PL muscle tendon is superficial at the retinaculum of the flexor muscles and is inserted in its anterior part, in the thenar eminence and in the palmar aponeurosis, with which it is continuous (Stecco et al, 2009). The extensor carpi radialis longus (ECRL) is fusiform and originates in the lateral supracondylar crest of the humerus (Lippert, 2006;Moore et al, 2010) and in the lateral intermuscular septum of the arm (Testut & Latarjet).…”
Section: Introductionmentioning
confidence: 99%